EVALUATION AND SPECIFICITY OF ISOKINETIC MUSCLE STRENGTH DURING ATHLETIC REHABILITATION AFTER ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION - YAMAMOTO, Toshiharu (Journal of The Showa Medical Association, 2000)
A new method was devised for evaluating the isokinetic muscle strength of athletes by means of a standard value ratio, which was derived from the mean value of muscle strength of 600 normal athletes at each test velocity expressed as a percentage of the relevant standard value. In the present study, the new method was tested on 25 athletes who had anterior cruciate ligament (ACL) reconstruction in order to progressively evaluate their course of muscle strength recovery until the return of the subjects to sports activity. As a result of employing the standard value ratio, it was possible to facilitate the comparison of the muscle strength recovery levels at each velocity by setting a fixed evaluation scale. The findings of the follow-up study were as follows. Although the recovery of muscle strength was observed to be concomitant with improvement of the activity level at each test velocity, the minimum value was seen at the velocity of 60 deg/sec at all activity levels. In particular, compared with other measured velocities, muscle strength at the time of returning to sports activity showed a 10-28% delay in recovery. These findings indicate that in the case of evaluating muscle strength recovery after ACL injury by evaluating the isokinetic muscle strength, it is more useful to evaluate the balance of recovery at each velocity rather than at a single velocity. Our findings indicate that in athletic rehabilitation after ACL reconstruction, especially at the time when an athlete returns to sports activity, it is essential to be aware of a delay in muscle strength recovery at slow speeds, such as 60 deg/sec at each velocity.